2003
DOI: 10.1128/mcb.23.17.6300-6314.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rad53 Phosphorylation Site Clusters Are Important for Rad53 Regulation and Signaling

Abstract: Budding yeast Rad53 is an essential protein kinase that is phosphorylated and activated in a MEC1-and TEL1-dependent manner in response to DNA damage. We studied the role of Rad53 phosphorylation through mutation of consensus phosphorylation sites for upstream kinases Mec1 and Tel1. Alanine substitution of the Rad53 amino-terminal TQ cluster region reduced viability and impaired checkpoint functions. These substitution mutations spared the basal interaction with Asf1 and the DNA damage-induced interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
129
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 76 publications
16
129
0
Order By: Relevance
“…3E, open arrowhead) in rad53-R70A-containing strains represents an important qualitative difference, suggesting that the FHA1 mutation leads to hyperphosphorylation of Rad53 on additional sites. This is supported by Western blots using a phospho-(S/T)Qspecific antibody that detects Rad53 phosphorylation by upstream kinases Mec1 and Tel1 (24,30,48). Although the total fraction of shifted Rad53 increased only by ϳ50% in the rad53-R70A-containing strains, HU-induced phosphorylation on (S/ T)Q sites was overproportionally increased by about 4-fold under these conditions (Fig.…”
Section: Fha1 Functions In the Mrc1 Pathwaymentioning
confidence: 81%
“…3E, open arrowhead) in rad53-R70A-containing strains represents an important qualitative difference, suggesting that the FHA1 mutation leads to hyperphosphorylation of Rad53 on additional sites. This is supported by Western blots using a phospho-(S/T)Qspecific antibody that detects Rad53 phosphorylation by upstream kinases Mec1 and Tel1 (24,30,48). Although the total fraction of shifted Rad53 increased only by ϳ50% in the rad53-R70A-containing strains, HU-induced phosphorylation on (S/ T)Q sites was overproportionally increased by about 4-fold under these conditions (Fig.…”
Section: Fha1 Functions In the Mrc1 Pathwaymentioning
confidence: 81%
“…Extensive studies have identified the role of Mec1 in the phosphorylation of Rad53 and a key role of Mrc1 in the recruitment of Rad53 after Mrc1 is phosphorylated by Mec1 for Rad53 activation (21,33). Both Mec1 and Mrc1 are known to be recruited to the DNA replication forks via distinct mechanisms; thus they are poised to exert their activities on Rad53, which is known to help maintain DNA replication forks in response to genotoxic stresses (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a direct and transphosphorylation of the N-terminal TQ sites of the Chk2 family kinases by the Mec1/ATR family kinases is also important for their activation in vivo. Analogous to the requirement of N-terminal TQ site phosphorylation of Chk2 by ATR in human (32), the activation of Rad53/Cds1 in vivo requires phosphorylation of TQ sites in their N termini by Mec1/Rad3 (33,34).…”
mentioning
confidence: 99%
“…An equivalent position in fission yeast Cds1, Thr-11, is phosphorylated by Rad3 in vitro and is required for Cds1 activation in vivo (16). Similarly, efficient activation of budding yeast Rad53 requires one or more N-terminal TQ motifs that are potential substrate phosphorylation sites of Mec1 (30).…”
mentioning
confidence: 99%